The Investigation of Ventilation Strategies on Indoor Thermal Comfort for a Classroom - Lee, Yee Hwee; Zakaria, Mohd Azuan (Recent Trends in Civil Engineering and Built Environment, 2024)
Classroom ventilation is crucial in creating an effecting environment for students and educators at the same time maintaining thermal comfort. The aim of this studies is to investigate the thermal performance of the recommended ventilation strategy (natural and hybrid ventilation) via field investigation in a classroom and to evaluate the thermal comfort of a classroom for each study case. The parameters of thermal comfort including air temperature, relative humidity, windspeed and globe temperature were assessed during the field measurement and analysed by using Predicted Mean Vote model. The results show the hybrid ventilation is proven to be the best ventilation scenario for classroom ventilation. The most comfortable case which is hybrid ventilation from 10.00 to 12.20 pm with range of PMV -0.08 to +0.5 whilst the other cases were above the comfort zone.